PEMANFAATAN BAMBU OLEH MASYARAKAT PENGRAJIN DESA MENYABO KECAMATAN TAYAN HULU KABUPATEN SANGGAU - Sinaga, Meysa Florensiani; M, Iskandar A; Thamrin, Eddy (Universitas Tanjungpura, 2019)
Bamboo is a very useful plant for people’s lives. Traditionality bamboo is commonly used for various purposes such as household utensils, handicrafts and construction materials for building houses and foodstuffs. The purpose of this study is to determine the types of bamboo and parts of the bamboo plant that are used, to find out in what form the benefits of the bamboo plant, to describe the types of product made from the bamboo plant that are used by the people of Menyabo Village of Tayan Hulu Subdistrict of Sanggau Regency. The method used in this study is a direct survey method in the field; data collection techniques were carried out through interviews using interview guidelines, and data were obtained using a descriptive method. The results of this study found 2 species of bamboo: Schizostacyum zollingeri Stuedel (reed bambbo) and gigantochloa balui K M Wong (abe bamboo). they use bamboo by craftsmen such as nyiruk, ketoro, atom, baskets, rice containers and jarai, home building construction materials and vegetable food ingredients (bamboo shoots). keywords: Bamboo, Craftsman, Utilization